Vibration change and crack propagation under bending vibration of aluminum alloy - Junji SAKAMOTO; Naoya TADA; Takeshi UEMORI (Nihon Kikai Gakkai ronbunshu, 2024)
In this study, aluminum alloy specimens were subjected to bending vibrations at different vibration frequencies near the first resonance frequency in order to investigate the vibration changes associated with crack propagation. Bending displacement, crack length, and strains at several parts of the specimen were measured during the bending vibration tests. As a result, it was confirmed that when the vibration frequency was lower than the initial first resonance frequency, the vibration amplitude increased with the crack length, and when the vibration frequency was higher than the initial first resonance frequency, the vibration amplitude decreased with an increase in the crack length. This is due to the decrease in the first resonance frequency due to the material damage. The relationship between the change of bending displacement amplitude and the crack length during vibration of the specimens can be organized using the slope (dΔεx2/dfv) of the relationship between the strain range and the vibration frequency for the undamaged specimen. This might be due to the strong correlation between the decrease in the first resonance frequency and the crack size when the crack initiation location is limited in the material. Moreover, based on the relationship between the change of bending displacement amplitude and the crack length, the stress intensity factor range (ΔK) was estimated by incorporating the load change into the crack length. By using the modified ΔK, the crack growth rate during bending vibration could be predicted.